Propagación sexual y clonal de Sacha Inchi (Plukenetia Volubilis L.) bajo condiciones in vitro - Barrera Rengifo, Obdulio (2007)
This research was conducted in the laboratory of plant tissue culture of the National University of San Martin - ". Sexual propagation and clone inchi sacha (Plukenetia Volubilis L) under in vitro conditions" Tarapoto, entitled, also had objectives: develop an efficient protocol for sexual propagation by embryos and cloned! through nodal segments, evaluating the behavior of seedlings and efficiency of the means employed study on induction and differentiation of axillary buds located at the nodal segments under in vitro conditions. an experimental design completely randomized for both tests, in test 1 (sexual propagation) was used was counted with 9 treatments and 10 observations, being the treatments seeds nine accessions (Ecotypes) from genebank national research institute and extension - INIEA "the future" _ in test 11 (! clone propagation) counted with 4 treatments and 5 replications, with treatments culture media with different hormone levels. The results showed that embryos of treatment T2 (C2) within 2 days of the 1st seed germinated and differed week, obtaining full and vigorous seedlings. In the case of clonal propagation t2 treatment and 0.05 to 0.10 ppm. Hormone concentration of BAP and NAA in the culture medium was presented the best result in terms of hormonal induction but not differentiation.